Resting-State Functional Connectivity of the Ageing Female Brain—Differences Between Young and Elderly Female Adults on Multislice Short TR rs-fMRI - Podgórski, Przemysław; Waliszewska-Prosół, Marta; Zimny, Anna; Sąsiadek, Marek; Bladowska, Joanna (Frontiers in Neurology, 2021)
Introduction: Age-related brain changes are one of the most important world health problems due to rising lifespan and size of the elderly populations. The aim of the study was to assess the effect of ageing in female adults on the coordinated brain activity between eight resting-state networks. Material and methods: Material comprises 60 healthy female volunteers who were split into two age groups: younger women (age 20-30 n=30) and older women (age 65-80 n=30). Resting-state data were collected during a 15 min sec scan in eye-closed condition using a 3T MR scanner. The study protocol consisted of a high-resolution sagittal T1-weighted sequence. Data were pre-processed and analysed using the CONN toolbox version 19.c. The vast network analysis included a priori selected regions of interest of default mode, sensorimotor, visual, salience, dorsal attention, fronto-parietal, language and cerebellar networks. Results: Within visual, default mode, salience as well as sensorimotor networks, the inter-network resting-state functional connectivity (RSFC) was significantly higher with older age. There was also a significant improvement in the between-network RSFC in older females compared to young females found in the following nodes of networks: sensorimotor lateral and salience, salience and language, salience and fronto-parietal, cerebellar anterior and default mode, cerebellar posterior and default mode, visual and sensorimotor lateral, visual and sensorimotor, visual lateral and default mode, language and cerebellar anterior, language and cerebellar posterior, fronto-parietal and cerebellar anterior, dorsal attention and sensorimotor, dorsal attention and default mode, sensorimotor superior and salience. Compared to young females, the elderly women presented significantly lower between-network RSFC bilaterally of the salience supramarginal gyrus and cerebellar posterior, sensorimotor lateral and cerebellar anterior network, sensorimotor lateral and cerebellar posterior as well as sensorimotor superior and cerebellar posterior network. Conclusion: Increased resting-state functional connectivity between some brain networks including visual, default mode, salience, sensorimotor, language, fronto-parietal, dorsal attention, as well as cerebellar anterior and cerebellar posterior networks in the elderly females may function as a compensation mechanism during the ageing process of the brain. To the best of our knowledge this study is the first that reports the importance of cerebellar networks improvement during healthy female ageing.